Pengaruh Price Discount, Fashion Involvement Dan Shopping Lifestyle terhadap Impulse Buying pada Pengguna Produk Fashion E-Commerce Shopee - Fatimatuz Zahro; Misti Hariasih; Lilik Indayani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to determine and analyze the effect of price discounts, fashion involvement and shopping lifestyle on increasing impulse buying on users of fashion products in e-commerce shopee. This research was conducted using quantitative methods and the population was people who were shopee E-commerce consumers and consumers aged 17 years and over. The sample determination was carried out using non-probability sampling techniques through purposive sampling method so that a sample of 96 respondents was obtained. The types of data in this study include primary data and secondary data, with data collection techniques using questionnaires. Data analysis in this study was carried out using SPSS version 25 which includes validity test, reliability test, classical assumption test (normality test, multicollinearity test, and heteroscedasticity test), multiple linear regression test, T test, and determination coefficient test (R2). So that the results obtained state that price discount, fashion involvement and shopping lifestyle have an effect on impulse buying.